The Conditions of the Environment as Factors Affecting the Social and Political Stability of Populations - Fausto Pedrazzini (Italian Journal of Agronomy)
In this review article, the different conditions of the environment which could affect the well-being of the populations living on it are taken into consideration and analysed. A specific attention is paid to the phenomenon of water reduction, land degradation and consequent desertification. Such a phenomenon is particularly worrying in selected regions of the world (the Mediterranean Region and Central Asia) in which a combination of several factors including climate variations, pressure of populations and increased competition for the available resources have a direct consequence on the economical, social and political conditions of the population. In addition, migrations could also take place, increasing the instability of entire regions. A proper management of water resources and the preservation of land and soil resources are essential requisites to counteract the mentioned adverse effects. Such a management is frequently a transboundary concern since it might involve different regions and countries; this is an additional reason for debating the environment degradation issues at the international level and for increasing the awareness of the civil society, the policy makers and governments.